The Pesantren Networking in Priangan (1800-1945) - Ading Kusdiana; Nina Herlina Lubis; Nurwadjah Ahmad EQ; Mumuh Muhsin Z (UIN Sunan Gunung Djati Bandung, 2013)
This research is about the networks of pesantren in Priangan from 1800 to 1945. The result shows that along 1800-1945, there were many networks that described the relations among pesantrens in Priangan. There are five networks forms as manifested from those relations. First, the networks among pesantrens, which were formed, are based on scientific relation. They are Pesantren Al-Falah Biru, Pangkalan and Keresek in Garut; Gentur, Kandang Sapi and Darul Falah Jambudipa in Cianjur; Sukamiskin Bandung; and Darul Ulum in Ciamis. Those pesantrens have intellectual relation that pointed to one public figure, namely Syekh Khatib Sambas in Mecca. Second, the networks among pesantrens, which were formed, are based on relative (genealogy) relations. The existence of Pesantren Sumur Kondang, Keresek, Gentur, and Cijawura were the ones that have this relation. Third, the networks among pesantrens, which were formed, are based onmarriage relation. For instance, Pesantren Cidewa with Pagerageung, Pesantren Cipari with Cilame, Cipasung with Gentur Rancapaku, Cijantung with Gegempalan, Sukamiskin with Al-Jawami, and Pesantren Sukamiskin with Cijawura Bandung, were the ones that have this relation. Fourth, the networks among pesantrens, which were formed, are based on the similarities in developing a particular Islamic mysticism (tarekat). The existence of Pesantren Suryalaya which develops Qodiriyah wa Naqsabandiyah mysticism—followed by generating their talqin and Pesantren Al-Falah Biru which develops Tijaniyah mysticism—followed by generating their muqaddam are the ones of this relation. Fifth, the networks among pesantrens, which were formed, are based on the same vision of their movement and struggle against the colonizer. The existence of Pesantren Al-Falah Biru with Samsul Ulum Gunung Puyuh through POII (Persatoean Oemat Islam Indonesia) organization, and Pesantren Cipasung with Sukamanah through Nahdhatul Ulama organization in Tasikmalaya were the ones who struggle against the colonizers of Netherland and Japan.